Interações planta-herbívoro-parasitoide mediadas por voláteis de melão, Cucumis melo L. - Silveira, Talita Antonia da (2018)
In melon crop there are some insects that can be considered key pests, as Bemisia tabaci biotype B (Gennadius, 1889). This insect causes direct damage by sap suction and indirect damage by virus transmission through the feeding activity. The main control method is chemical, but alternatives such as the use of volatiles involved in the tritrophic interactions of this insect have been studied. One of these interactions involves the search of the parasitoid by its host, using volatiles emitted by the plant and also by the host. The objective of this study was to investigate and identify volatile compounds released by the melon plant when attacked by B. tabaci and to verify the response of this insect and the parasitoid Encarsia desantisi to the volatiles of the plant. The attractiveness of B. tabaci to healthy melon plants, infested melon plants (by B. tabaci) and control (clean air) was tested in a 4-way olfactometer. The retention time of B. tabaci was higher for the volatiles of healthy plants than in the control (clean air). In addition, B. tabaci showed higher number of entries and longer retention times in the control (clean air) in relation to infested plants. With the chance of choosing between odors from healthy plants, infested plants and control, B. tabaci adults spent more time in control, followed by infested plants and healthy plants. For the behavioral response of E. desantisi, were evaluated: the volatiles of healthy melon plants vs control; infested plants vs control and healthy plants vs. infested plants vs control. Females of E. desantisi remained longer in plants infested by B. tabaci than in control (clean air). There were no differences in time spent by parasitoid females in healthy plant odors and in control (clean air). When comparing the response of the parasitoid to infested plants, healthy plants and clean air, there was a greater time spent in plants infested by B. tabaci odors in relation to the control (clean air). The volatiles of healthy and infested melon plants were collected for 24 hours, and 12 compounds were identified. Methyl Salicylate and Tetradecane were found only in infested plants. The attractiveness of E. desantisi to synthetic compounds (α-Pinene, β-Pinene, β-Myrcene, Ocimene, Salicylate Methyl and Tetradecane) indicated that there was no difference in the time spent by the parasitoid females in relation to the control (clean air). B. tabaci nymphs wash was tested for E. desantisi attractiveness and showed to be biologically active, with the 50% ether fraction being active for the parasitoids. The 50% ether fraction was refracted, and in the bioassays the 10% ether fraction showed biological activity. The results analyzed in GC-FID and GC/MS characterized the compounds as belonging to two classes: esters and ketones.